Genetic Analysis Of Rhododendron Mutants Using Random Amplified Polymorphic DNA (RAPD) - Açık, Leyla; ATAK, ÇİMEN; ÇELİK, ÖZGE (Pakistan Botanical Soc, Dept Of Botany Univ Karachi, 32 Karachi, Pakistan, 2011)
The aim of our study was to consider the efficiency of randomly amplified polymorphic DNA (RAPD) analysis to show the differences between Rhododendron mutants and control plants. The mutant plantlets were selected due to their better In vitro shoot and root regeneration relative to control in both varieties. Six mutant plantlets from Alfred and seven mutant plantlets from Paars variety were selected from M(1)V(2) generations. These mutants were selected from plantlets which were irradiated with doses 5 and 10 Gy. They were grown up In vitro conditions. The dendrogram shows one big cluster and the others to be distinguished. Genetic variability induced with gamma ray and RAPD methods were used to detect mutations at the Rhododendron shoot culture. Our results show that Rhododendron mutants were district from controls.
Keywords: in-vitro mutagenesis; shoot regeneration; gamma-radiation; markers; variability; mutations; diversity; cytokinin; cultivars; radiomutants; sürgün rejenerasyonu; y-radyasyon; belirteçler; değişkenlik; mutasyonlar; çeşitlilik; sitokinin; çeşitlerin